Epidemiological situation of mycobacterioses in Ukraine and the worldwide at the beginning of the 21st century: A literature review - Panivska, Olha V.; Shevchuk, Viktor M. (My University, 2024)
The lack of a unified reporting system for clinical outbreaks of mycobacterioses makes it difficult to objectively assess the epidemiological situation and identify patterns in the epidemic process, despite the growing relevance of this issue in human and veterinary medicine. The aim of this review was to study the epidemiological and aetiopathogenetic aspects of mycobacterioses in Ukraine and other countries on different continents. A comparative-geographic method and epidemiological analysis method were used in the study. As a result, it was found that in Ukraine, mycobacterioses in humans are widespread, with 94% of cases manifesting as pulmonary forms, often forming mixed infections with tuberculosis, making them difficult to diagnose. The most common aetiological factor is M. avium complex and disseminated mycobacteriosis usually develops in HIV-infected patients. In most of the analysed countries (Japan, South Korea, Iran, Turkey, Pakistan, Saudi Arabia, Egypt, Oman, Kuwait, China, France, Great Britain, Italy, Greece, Czech Republic, Poland, USA, Canada, Brazil, Australia and several African countries) during the period 2000-2023, there was an observed increase in the incidence of lung diseases caused by non-tuberculous mycobacteria, including an 8-fold rise in South Korea; an annual growth of 8% in the USA; and a 2.3-fold increase in Queensland (Australia) from 11.1 pcm in 2001 to 25.88 pcm in 2016. It was established that the epidemiological features of mycobacterioses are the predominant infection of patients with rapidly growing mycobacteria; an increased risk of mycobacterial infection with increasing age; detection of M. avium complex, M. abscessus complex, M. kansasii and M. fortuitum as the most common cause of mycobacterioses
Keywords: human mycobacterioses; nontuberculous mycobacteria; epidemiology of mycobacterioses; M. avium complex; 616.98(477+100)